Wheat bran levels for growing and finishing swine rations - Fialho, Elias T.; Gomes, Paulo Cesar; Bellaver, Claudio; Protas, José Fernando da S.; Costa, Valdomiro (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at the Centro Nacional de Pesquisa de Suínos e Aves (CNPSA) of EMBRAPA, at Concórdia, SC, Brazil, in June of 1983., using 168 pigs of both sexes, with 23.6 kg initial and 94.5 kg final weight. A completely randomized block design with seven treatments and four replications was used. The treatments were: A. 0% - 0%; B. 0% - 15%; C. 0% - 30%; D. 0% - 45%; E. 10% - 15%; F. 20% - 30% e G. 30% - 45% of wheat bran (WB) in the rations for growing and finishing pigs, respectively. The average daily weight gain (ADWG) was not influent (P>0.05) by the WB tested levels. Pigs fed 0% - 30%, 10% - 15% and 20% -30% WB rations were not significantly different (P>0.05) in daily feed intake (DFI) but their DFI was significantly lower (P<0.05) in relation to those fed 30% - 45%WB rations. Feed conversion (FC) was lower (P<0.05) for pigs fed 0% - 0%; 0% - 15%, 0% - 30% and 10% - 15% WB rations. The WB levels did not significantly affect carcass characteristics (P<0.05). The values of brute protein (BP) digestibility and of digestible energy of the rations were significantly reduced (P<0.05) with increasing WB levels. It was concluded that the WB level up to 25% in growing, and 30% in finishing rations did not affect the performance or pigs.